Предмет: Математика,
автор: kkeeperofdreams
(x-1)^2-(11-x)^2
Помогите пожалуйста
Ответы
Автор ответа:
0
x^2-2x+1-121+22x-x^2=20x-120= 20(x-60)
Автор ответа:
0
(х-1)^2 - (11-х)^ =
= х^2 - 2х + 1 - (121 - 22х + х^2) =
= х^2 - 2х + 1 -121 + 22х - х^2 =
= 20х - 120 = 20(х-6)
= х^2 - 2х + 1 - (121 - 22х + х^2) =
= х^2 - 2х + 1 -121 + 22х - х^2 =
= 20х - 120 = 20(х-6)
Похожие вопросы
Предмет: Геометрия,
автор: Hellomynameis17
Предмет: Английский язык,
автор: ppopova174
Предмет: История,
автор: chelovekovich05
Предмет: История,
автор: playmarket1505